SAT-188 An Unusual Case Of Intra-adrenal Purely Norepinephrine Secreting Pheochromocytoma - de Souza, Tamara Gizelle (J Endocr Soc, 2020)
Background: In 40% of pheochromocytoma/paraganglioma (PPGL) cases a causal germline mutation in a well-defined gene can be identified. The remainder are sporadic. The most common hereditary syndromes are NF1, MEN2 and VHL. Paragangliomas usually produce exclusively norepinephrine (NE) and are more likely to metastasize than adrenal tumors. Exclusively NE producing adrenal tumors are extremely rare and almost always associated with VHL or SDH syndromes (1). Clinical Case: A 45-year-old South Asian woman with a 5-year history of HTN controlled on losartan presented emergently complaining of chest pressure. Cardiovascular workup was unrevealing. CT chest showed an incidental 3.2 x 2.4 cm lipid-poor left adrenal adenoma. No further follow-up done at that time. Two years later she presented with recurring episodes of chest pressure and uncontrolled HTN on amlodipine, metoprolol and losartan. She denied panic attacks, diaphoresis and other symptoms of anxiety. She denied personal and familial history of clinical features seen in NF1, MEN 2, VHL or SDH. Plasma metanephrines were 26 (<=57 pg/mL) and free normetanephrine 902 (<=148 pg/mL). 24-hour urine metanephrine was 178 (58-203 mcg/24h), normetanephrine 2422 (88-649 mcg/24h) and total metanephrine 2600 (182-739 mcg/24h) confirming the diagnosis of a solely NE secreting PPGL. MRI abdomen showed a well-circumscribed 3.3 cm lipid-poor left adrenal mass. MIBG scan and SPECT CT showed a focal area of intense radiotracer uptake corresponding to a 3.2 x 2.5 cm mass within the left adrenal gland. No extra-adrenal activity was demonstrated. Alpha blockade was started with doxazosin and the patient asked to salt/fluid load. She underwent left adrenalectomy. Pathology revealed a 5 x 2.5 x1.1 cm intra-adrenal pheochromocytoma; Chromogranin (+), synaptophysin (-), MIB1 low reactivity < 5%, S100 positive in sustentacular cells, keratin (-), EMA (-), Inhibin (-). Genetic testing for VHL, SDHD, SDHB, SDHC and MAX has been ordered per guidelines. One month post-operatively the patient had no symptoms of adrenergic overactivity and normal plasma metanephrine levels. Clinical Lessons: This rare case of norepinephrine-only secreting pheochromocytoma is made even more unusual by absence of features of autosomal dominant hereditary syndromes. This may be sporadic or present a novel VHL, SDHD, SDHB, SDHC or MAX germline mutation (2). 1. Eisenhofer, G., et al., Distinct gene expression profiles in norepinephrine- and epinephrine-producing hereditary and sporadic pheochromocytomas: activation of hypoxia-driven angiogenic pathways in von Hippel–Lindau syndrome. 2004. 11(4): p. 897. 2. Ercolino, T., et al., Uncommon clinical presentations of pheochromocytoma and paraganglioma in two different patients affected by two distinct novel VHL germline mutations. Clinical Endocrinology, 2008. 68(5): p. 762-768.